Manajemen Kebijakan Pendidikan Islam Pada Era Digital: Tantangan Tata Kelola di SMA Al Hijrah Global School - Anysah Daulay; Elvi Risky; Hasti Ananda; Tengku Darmansyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of the digital era has brought significant changes to the world of education, including Islamic education, thus requiring educational institutions to adapt their policies and governance in a more modern way without neglecting Islamic values. SMA Al Hijrah Global School, as a globally oriented Islamic school, faces challenges in integrating the use of technology with the principles of Islamic education, both in learning, administration, and character development of students. This study aims to analyze how Islamic education policies are managed in the digital era and to identify the main challenges that arise in digital governance at the school.This research uses a descriptive qualitative approach with a case study design, involving the principal, teachers, administrative staff, and students as informants selected through purposive sampling. Data were collected through interviews, observations, and documentation, and then analyzed using the Miles and Huberman model. The findings show that the school has utilized technology in learning and management; however, it still faces constraints in the form of limited digital competence among teachers, suboptimal infrastructure, and challenges in supervising students’ digital ethics. The implications of this study indicate the need to strengthen Islamic education policies that are more adaptive to digital developments through improving digital literacy, providing adequate infrastructure, and reinforcing digital ethics based on Islamic values so that educational governance can run effectively and in line with the demands of the digital era.